2021
DOI: 10.1080/15376494.2021.1949509
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of mechanical properties and energy absorption capabilities of functionally graded and non-graded thermoplastic sheet gyroid structures

Abstract: Comparative analysis of mechanical properties and energy absorption capabilities of functionally graded and non-graded thermoplastic sheet gyroid structuresAdditive manufacturing allows the tailoring of the structure of energyabsorbing materials. It is thus feasible now to use light, printed structures instead of other materials such as foams and honeycombs, signifying greater possibilities for customization. Some of these structures are triply periodic minimal-surface structures that is a family of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Mechanical tests were repeated 3 times for all volume fractions cell sizes and strain rates. Only small deviation of the results were observed in the stress strain curves as confirmed by the groups previous studies [10,17,32,33] (a selection of some of the results of the study of the variability are shown in Table 1). The low deviation could be due to aspects such as the control of the temperature of the room and of the printing space, the use of the same roll of material for the identical specimens, the use of the same printing machine and that the specimens have been printed and tested consecutively.…”
Section: 𝑊 = ∫ 𝜎(𝜀) 𝑑𝜀supporting
confidence: 82%
See 2 more Smart Citations
“…Mechanical tests were repeated 3 times for all volume fractions cell sizes and strain rates. Only small deviation of the results were observed in the stress strain curves as confirmed by the groups previous studies [10,17,32,33] (a selection of some of the results of the study of the variability are shown in Table 1). The low deviation could be due to aspects such as the control of the temperature of the room and of the printing space, the use of the same roll of material for the identical specimens, the use of the same printing machine and that the specimens have been printed and tested consecutively.…”
Section: 𝑊 = ∫ 𝜎(𝜀) 𝑑𝜀supporting
confidence: 82%
“…These mechanical properties can be modified by controlling the density during the foaming process [1,2]. Some researchers concluded that this behavior mode applies to corks and cork products [10] and lattice structures [17].…”
Section: 𝑊 = ∫ 𝜎(𝜀) 𝑑𝜀mentioning
confidence: 99%
See 1 more Smart Citation
“…Energy absorption diagrams are used to evaluate the optimal energy absorption capacity of cushioning packaging materials with different densities at different strain rates under a certain stress level. In cushioning packaging design, through energy absorption diagrams, the geometric dimensions and the most suitable density of cushioning materials can be optimized and chosen [20,23]. So, it is very valuable to draw the energy absorption diagrams of closed-cell EVA foams for cushioning packaging optimization design.…”
Section: Energy Absorption Diagrammentioning
confidence: 99%
“…To further exploit the advantages of the energy absorption capability of the lattice structure, many researches have carried out gradient design on the lattice structures, such as sheet‐based G, [ 16 ] sheet‐based P [ 17 ] and face‐centered cubic (FCC). [ 18 ] Gao et al [ 19 ] conducted linear and nonlinear gradient design for BCC structure with the same relative density.…”
Section: Introductionmentioning
confidence: 99%